The Relationship Between Husband Support and Antenatal Care Visits Among Pregnant Women in the Third Trimester at PMB Nelly in Padangsidimpuan In 2024 - Rya Anastasya Siregar; Rizka Heriansyah; Tapi Endang Fauziah Lubis; Arisa Harfa Said Lubis; Novita Sari Batubara; Nur Aliyah Rangkuti (International Journal of Public Health Excellence (IJPHE), 2026)
Prenatal care, or prenatal checkups at the nearest medical facility, can evaluate the health of pregnant women.Husband's support is one element that influences the frequency of prenatal care visits. Matemal mortality can be avoided with more prenatal care visits. This study aims to determine the relationship between prenatal care visits and husband's support among third-trimester pregnant women at PMB Nelly, Padangsidimpuan City in 2024. This study used a cross-sectional and quantitative approach. A total of 32 people were selected using an accidental sampling method. The results showed that the majority of husbands (18 people) did not provide assistance, and the mejority (20 people, or 62.5%) did not attend scheduled prenatal care appointments. A significant correlation between husband's support and prenatal care visits among third-trimester pregnant women was found using the chi-square test, which produced a p-value of 0.006. Conclusion: Among third-trimester egnant women, there is a relationship between prenatal care visits and husband's support. Recommendation: Husbands can help their wives to continue with prenatal care by increasing their involvement, and pregnant women should understand the importance of completing all planned ANC examinations as decided by health professionals.